Meteorin: a secreted protein that regulates glial cell differentiation and promotes axonal extension - Nishino, Jinsuke (Nature Publishing Group, 2004)
Glial cells are major components of the nervous system. The roles of these cells are not fully understood, however. We have now identified a secreted protein, designated Meteorin, that is expressed in undifferentiated neural progenitors and in the astrocyte lineage, including radial glia. Meteorin selectively promoted astrocyte formation from mouse cerebrocortical neurospheres in differentiation culture, whereas it induced cerebellar astrocytes to become radial glia. Meteorin also induced axonal extension in small and intermediate neurons of sensory ganglia by activating nearby satellite glia. These observations suggest that Meteorin plays important roles in both glial cell differentiation and axonal network formation during neurogenesis.